Participation of the agonist and antagonist knee extensor muscles in drop kick, placing kick and up and under kick, in rugby athletes - Dias, Inês (2019)
Poster presented at the 3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. 20-22 June 2019, Campus Egas Moniz, Monte de Caparica, Portugal